Comparative Analysis of Wealth Redistribution: Fiscal Instruments of the Prophet's Era and Indonesia's Fiscal Policy in Poverty Reduction - Siti Itsna Syamsiyah; Muhamad Agus Alfiyan Nur Ahmada; Muhamad Aqim Adlan; M. Arif Faizin (PT. INOVASI TEKNOLOGI KOMPUTER, 2026)
This study aims to analyze the comparative study of wealth redistribution from fiscal instruments from the Prophet Muhammad's era and Indonesian fiscal policy in poverty alleviation. Using qualitative research methods with a literature review approach, it was found that the Islamic financial system has had a clear, structured framework, and a social justice orientation since its inception. Zakat is a key pillar, not only an individual act of worship but also a fiscal instrument managed by the state through the Baitul Mal (the Islamic treasury). In addition to zakat, there are other sources such as ghanimah, fai', jizyah, kharaj, usyr, khums, as well as voluntary contributions in the form of infaq, sadaqah, and waqf. When compared with modern Indonesian fiscal policy, there are fundamental differences both in revenue sources and management mechanisms. Indonesia places taxes as the fiscal backbone. The comparative analysis shows that the Prophet Muhammad's fiscal system excels in aspects of target certainty, mechanism simplicity, and a strong moral-spiritual foundation. Meanwhile, the Indonesian fiscal system excels in aspects of modern institutions, legal frameworks, and the ability to manage a more complex economic scale. Indonesia's biggest challenge is how to bridge the Islamic values ​​of social justice with contemporary fiscal policy practices